The study of thyroid profile in abnormal uterine bleeding at tertiary care center, Rajasthan, India - Gurjar, Dinesh; Pachori, Purnima; Chaudhary, Sandhya; Singh, Dharmendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypothyroidism and Hyperthyroidism leads to menstrual irregularities. Females with thyroid gland abnormality have chances of reproductive abnormalities ranging from abnormal sexual development, menstrual irregularities, infertility and premature menopause. The objectives were to study the association between thyroid dysfunction and AUB in the reproductive age group (18-45 years), To study the thyroid abnormalities in different types of AUB in the reproductive age group, to establish if screening for thyroid abnormalities is justified using T3, T4 and TSH. Methods: This cross-sectional study conducted among 250 women with ‘abnormal uterine bleeding’ (AUB). Inclusion criteria for participants were females in the age group of 18-45 years, females presenting with abnormal uterine bleeding, with thyroid dysfunction, females who do not have signs of demonstrable pelvic pathologyincluding PID. Results: Majority of the patients belonged to the age group of 24 - 32 years i.e.56.8%, 9.2% cases were nullipara, 44.0% cases have menorrhagia, 32.2% have oliogomennorrhea, 19.6% have amenorrhea. Around 3.6% had Thyromegaly, 12.4% have weight gain in hypothyroidism, 28.4% have fatigue in hyperthyroidism, 6.8% cases have higher T4 level, 18.0% cases have higher TSH level. Conclusions: The risk of progression to overt hypothyroidism (about 5% per year) in patients with subclinical disease and the cost-benefit ratio also emphasises the need for selective screening. Early detection of subclinical disease by selective screening facilitates appropriate therapy early in the course of the disease.